Evaluation of Non-Point Source Pollution Load Characteristics and Identifying Management Sub-Basin Area and Best Management Practices Using HSPF Model in Yongdam Dam Watershed - Choi, Yong-Ho; Jeong, Yong-Hoon; Nguyen, Hong-Hue Thi; Yoon, Seung-Hyun; Yi, In-Gyong; Kwak, Dong-Heui (Daehan hwan'gyeong gonghag hoeji, 2023)
Objectives : To identify and estimate the non-point source (NPS) pollution loads in the Yongdam watershed, and to take an appropriate NPS management plan suitable for the environmental conditions of the sub-basin of Yongdam watershed.Methods : The NPS pollutant loads of the Yongdam watershed was investigated to establish the hydrological simulation program-fortran (HSPF) model for the study area so that the characteristics of non-point runoff were simulated. Furthermore, the detailed catchment area subject to non-point pollution management was selected and the effect of reducing non-point pollution was examined based on the various simulation results.Results and Discussion : The three sub-basins, including specific component of catchments, of Yongdam watershed was selected according to the load intensity and distribution of NPS pollution. The result of analyzing the load flowing into the downstream by rainfall intensity revealed that the pollutant load accounted for 11.8~19.9% in the dry season, and for Jinan-cheon sub-basin the load was high in the range of 10~30 mm while Janggye-cheon sub-basin and downstream of Janggye-cheon junction sub-basin showed a high load in the range 30~60 mm. In addition, the load duration curve (LDC) showed the excess frequency of BOD load was high when the flow rate increased at the end of stream for each sub-basin, whereas the load excess frequency was high in T-P in the entire flow range. LDC analysis led to us that the water quality of stream was affected by point and non-point pollutants in a complex way. When the ground cover in a farm were installed by selecting 10 detailed catchments with high need for NPS pollution management, the reduction of T-P load was estimated to be reduced by 325.256~995.912 g/d in Jinan-cheon sub-basin, 1279.813~3327.513 g/d in Janggye-cheon sub-basin, and 1316.831~3555.443 g/d in downstream of Janggye-cheon junction sub-basin.Conclusion : Through various simulation experiments using the HSPF model, it was feasible to select an catchment subject to NPS pollution control in detail and evaluate the effect of reducing NPS pollution.